Flow cytometry-based platelet function testing is predictive of symptom burden in a cohort of bleeders. (4th July 2018) - Boknäs, Niklas; Ramström, Sofia; Faxälv, Lars; Lindahl, Tomas L.
Abstract: Platelet function disorders (PFDs) are common in patients with mild bleeding disorders (MBDs), yet the significance of laboratory findings suggestive of a PFD remain unclear due to the lack of evidence for a clinical correlation between the test results and the patient phenotype. Herein, we present the results from a study evaluating the potential utility of platelet function testing using whole-blood flow cytometry in a cohort of 105 patients undergoing investigation for MBD. Subjects were evaluated with a test panel comprising two different activation markers (fibrinogen binding and P-selectin exposure) and four physiologically relevant platelet agonists (ADP, PAR1-AP, PAR4-AP, and CRP-XL). Abnormal test results were identified by comparison with reference ranges constructed from 24 healthy controls or with the fifth percentile of the entire patient cohort. We found that the abnormal test results are predictive of bleeding symptom severity, and that the greatest predictive strength was achieved using a subset of the panel, comparing measurements of fibrinogen binding after activation with all four agonists with the fifth percentile of the patient cohort ( p  = 0.00008, hazard ratio 8.7; 95% CI 2.5–40). Our results suggest that whole-blood flow cytometry-based platelet function testing could become a feasible alternative for the investigation of MBDs. We also show that platelet function testing using whole-blood flow cytometry could provide a clinically relevant quantitative assessment of platelet-related hemostasis.